Islet Compensation in Metabolic Stress: Lessons from Animal Models - Singh, Himadri (Current Diabetes Reviews, 2016)
Type 2 diabetes is characterized by decreased functional beta-cell mass, as a consequence of metabolic stress associated with obesity, aging, insulin resistance and pregnancy. The metabolic stress is caused by increased insulin demand, pro-inflammatory cytokines, and free fatty acids. Fortunately, islets have remarkable property to adapt to increased metabolic demand. This review focuses on the mechanisms of islet adaptation to metabolic stress in obesity and insulin resistance
Keywords: Islets